Relaxin Deficiency Leads to Uterine Artery Dysfunction During Pregnancy in Mice - Marshall, Sarah A.; Senadheera, Sevvandi N.; Jelinic, Maria; O'Sullivan, Kelly; Parry, Laura J.; Tare, Marianne (Frontiers in Physiology, 2018)
The uterine vasculature undergoes profound adaptations in response to pregnancy. Augmentation of endothelial vasodilator function and reduced smooth muscle reactivity are factors contributing to uterine artery adaptation and are critical for adequate placental perfusion. The peptide hormone relaxin has an important role in mediating the normal maternal renal vascular adaptations during pregnancy through a reduction in myogenic tone and an increase in flow-mediated vasodilation. Little is known however about the influence of endogenous relaxin on the uterine artery during pregnancy. We tested the hypothesis that relaxin deficiency increases myogenic tone and impairs endothelial vasodilator function in uterine arteries of late pregnant relaxin deficient (Rln-/-) mice. Reactivity of main uterine arteries from non-pregnant and late pregnant wild-type (Rln+/+) and Rln-/- mice was studied using pressure and wire myography and changes in gene expression explored using PCR. Myogenic tone was indistinguishable in arteries from non-pregnant mice. In late pregnancy uterine artery myogenic tone was halved in Rln+/+ mice (P < 0.0001), an adaptation that failed to occur in arteries from pregnant Rln-/- mice. The role of vasodilator prostanoids in the regulation of myogenic tone was significantly reduced in arteries of pregnant Rln-/- mice (P = 0.02). Agonist-mediated endothelium-dependent vasodilation was significantly impaired in non-pregnant Rln-/- mice. With pregnancy, differences in total endothelial vasodilator function were resolved, although there remained an underlying deficiency in the role of vasodilator prostanoids and alterations to the contributions of calcium-activated K+ channels. Fetuses of late pregnant Rln-/- mice were approximately 10% lighter (P < 0.001) than those of Rln+/+ mice. In conclusion, relaxin deficiency is associated with failed suppression of uterine artery myogenic tone in pregnancy, which likely contributes to reduced uteroplacental perfusion and fetal growth restriction.